Geochemistry and rare-metal potential of coals of the Sakhalin coal basin, Sakhalin island, Russia; International Journal of Coal Geology; Vol. 268 - Arbuzov S. I. Sergey Ivanovich; Chekryzhov I. Yu. Igor Yurjevich; Verkhoturov A. A. Aleksey Aleksandrovich; Spears D. A. David Alan; Melky V. A. Vyacheslav Anatoljevich; Zarubina N. V. Nataljya Vladimirovna; Blokhin M. G. Maksim Gennadjevich (2023, 2023)
Title screen